1970
DOI: 10.5962/bhl.part.75922
|View full text |Cite
|
Sign up to set email alerts
|

Les fondements de la taxonomie des Strigeata La Rue (Trematoda: Strigeida)

Abstract: Dans cette Synopsis, les Cyathocotylinae et les Braunininae s'opposent aux autres sous-familles par la possession d'une poche du cirre. Les Strigeinae sont caractérisés par leur segment antérieur cupuliforme, contenant un « holdfast organ variously developed but always prominent ». La grande sous-famille des Polyeotxlinae réunit des parasites d'Oiseaux et de Reptiles, tandis que celle des Alariinae groupe ceux de Mammifères. La première s'oppose à la seconde par la forme de l'organe adhésif: « usually circular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 8 publications
0
6
2
Order By: Relevance
“…Despite similarities in larval and adult morphology, Dubois (1970) rejected the placement of Fibricola as a subgenus of Neodiplostomum and insisted that the distribution of vitellarium and specificity to mammals were sufficient for separation between the two genera. In spite of his own statement, Dubois (1983) placed N. vaucheri collected from a chiropteran host into Neodiplostomum .…”
Section: Discussionmentioning
confidence: 99%
“…Despite similarities in larval and adult morphology, Dubois (1970) rejected the placement of Fibricola as a subgenus of Neodiplostomum and insisted that the distribution of vitellarium and specificity to mammals were sufficient for separation between the two genera. In spite of his own statement, Dubois (1983) placed N. vaucheri collected from a chiropteran host into Neodiplostomum .…”
Section: Discussionmentioning
confidence: 99%
“…Its members parasitize, as adults, a variety of avian and mammalian definitive hosts worldwide. Despite the large number of studies on the Crassiphialinae, the systematics of the subfamily is complex and has always been unstable ( Dubois, 1970 ; Shoop, 1989 ; Niewiadomska, 2002 ). Therefore, the use of DNA sequence data for phylogenetic inference and taxon differentiation within the Crassiphialinae is highly beneficial.…”
Section: Introductionmentioning
confidence: 99%
“…As life cycles became better known, Cort (1917), Stunkard (1946) and others increasingly emphasized other characters, particularly cercarial morphology. Using a variety of methods, different authors produced conflicting hypotheses and higher classifications, but many concluded a close relationship exists among members of the Diplostomoidea Poirier, 1886, the Clinostomatoidea Lühe, 1901, and the Schistosomatoidea Stiles and Hassall, 1898 (Brooks et al, 1985;Dubois, 1970a;Gibson, 1996;La Rue, 1957;Pearson, 1972). Most authors assigned these and other superfamilies to the Strigeida (=Strigeatoidea) La Rue 1957, which are characterized by furcocercous cercariae that penetrate hosts (Gibson and Bray, 1994).…”
Section: Introductionmentioning
confidence: 99%